2005
DOI: 10.1027/1016-9040.10.4.320
|View full text |Cite
|
Sign up to set email alerts
|

Positive Adult Personality Development

Abstract: Abstract. Does personality stay stable after young adulthood or is there continued change throughout middle and later adulthood? For decades, this question has caused heated debate. Over the last couple of years, a consensus has emerged based on recent cross-cultural as well as longitudinal evidence. This consensus confirms that indeed there is personality change in middle and later adulthood. Many authors have labeled this change personality maturation or growth. In somewhat simplified terms the observed patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
129
2
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(148 citation statements)
references
References 68 publications
12
129
2
5
Order By: Relevance
“…Baltes, 1987Baltes, , 1997. However, scholars from various disciplines suggested that mental health contributes to successful aging because it helps older individuals to obtain, protect, and replenish other important personal resources such as competencies and social networks (Hobfoll & Wells, 1998;Keyes, 2007;Knight, Kaskie, Shurgot, & Dave, 2006;Lazarus & Delongis, 1983;Staudinger & Kunzmann, 2005;Warr, 1997). Mental health is also positively related to learning motivation (Colquitt, LePine, & Noe, 2000).…”
Section: The Role Of Mental Healthmentioning
confidence: 99%
“…Baltes, 1987Baltes, , 1997. However, scholars from various disciplines suggested that mental health contributes to successful aging because it helps older individuals to obtain, protect, and replenish other important personal resources such as competencies and social networks (Hobfoll & Wells, 1998;Keyes, 2007;Knight, Kaskie, Shurgot, & Dave, 2006;Lazarus & Delongis, 1983;Staudinger & Kunzmann, 2005;Warr, 1997). Mental health is also positively related to learning motivation (Colquitt, LePine, & Noe, 2000).…”
Section: The Role Of Mental Healthmentioning
confidence: 99%
“…Whereas wise reasoners may not necessarily be happier people (consistent with Staudinger & Kunzmann, 2005), wiser reflection on a concrete situation at hand may in fact be aligned with psychological benefits of more adaptive emotion regulation and greater satisfaction with one's life (Gross & Thompson, 2007;Kekes, 1983Kekes, , 1995Kross & Ayduk, 2011). In a given situation, focusing on sustaining one's well-being may be a healthy tendency.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…First, it suggests that any theoretical claims about the relationship between wisdom and various well-being enhancing or prosocial tendencies ought to consider the level of analysis. For instance, consider the debate about the role of wisdom-related characteristics for various markers of subjective well-being (for review, see Grossmann, 2017): Whereas some scholars suggest that wisdom may promote more positive emotions and greater life satisfaction (e.g., Bergsma & Ardelt, 2012), other scholars proposed that wisdom is linked with a deeper understanding of twists and turns of one's life, and therefore may not necessary contribute to one's subjective feeling of happiness (Staudinger & Kunzmann, 2005). Importantly, in most of these cases wisdom-related characteristics were measured only once, thus it is unclear whether effects concerned trait-or state-level associations between wisdom and happiness/mood, or could even be accounted by various additional situational contingencies (e.g., desire to present oneself in a positive light; Zacher et al, 2013).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…In the following, as we characterize gains and losses in life span development of self and personality, we use two approaches (see also Staudinger & Kunzmann, 2005). A first is based on evaluating developmental changes with regard to the adaptivity and functionality of the outcome for the individual, be it from a subjective (e.g., subjective well-being) or an objective perspective (e.g., longevity).…”
Section: Personality Development As Lifelong Transactional Adaptationmentioning
confidence: 99%